Identification of quantitative trait loci (QTLs) and candidate genes for seed shape and 100-seed weight in soybean [Glycine max (L.) Merr.] - Kumar, Rahul; Saini, Manisha; Taku, Meniari; Debbarma, Pulak; Mahto, Rohit Kumar; Ramlal, Ayyagari; Sharma, Deepshikha; Rajendran, Ambika; Pandey, Renu; Gaikwad, Kishor; Lal, S. K.; Talukdar, Akshay (Frontiers in Plant Science, 2023)
Soybean [Glycine max (L.) Merr.] is an important legume, which is rich in both edible oil and protein and grown for food, feed and industrial uses. One of the most crucial characteristics affecting soybean productivity is seed weight and seed shape, which is also desirable for speciality soy foods like tofu, natto, miso, and edamame. In order to find stable quantitative trait loci (QTLs) and candidate genes for seed shape and 100-seed weight, the current study used vegetable type and seed soybean-derived F2 and F2:3 mapping populations. A total of 42 QTLs were mapped, which were dispersed across 13 chromosomes. Of these, seven were determined to be stable QTLs in both the F2 and F2:3 mapping populations, and five of them were major QTLs, namely qSL-10-1, qSW-4-1, qSV-4-1, qSLW-10-1, and qSLH-10-1. Thirteen of the 42 QTLs detected in the current study were found at known loci, while the remaining 29 were discovered for the first time. Out of these 29 novel QTLs, 17 were major QTLs. Based on Protein Analysis Through Evolutionary Relationships (PANTHER), gene annotation information, and literature search, 35 genes within 7 stable QTLs were predicted to be possible candidate genes that might regulate seed shape and seed-weight in soybean. The current study identified the key candidate genes and quantitative trait loci (QTLs) controlling soybean seed shape and weight, and these results will be very helpful for marker-assisted breeding of soybean varieties with improved seed-weight and desired seed shape.